1985
DOI: 10.1128/aem.49.5.1270-1275.1985
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Streptococcus sanguis CH3 to polymers with different surface free energies

Abstract: The adhesion of the oral bacterium Streptococcus sanguis CH3 to various polymeric surfaces with surface free energies (-ys) ranging from 22 to 141 erg cm-2 was investigated. Suspensions containing nine different bacterial concentrations (2.5 x 107 to 2.5 x 109 cells per ml) were used. After adhesion for 1 h at 21°C and a standardized rinsing procedure, the number of attached bacteria per square centimeter (nb) was determined by scanning electron microscopy. The highest number of bacteria was consistently found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
5

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(37 citation statements)
references
References 21 publications
2
29
1
5
Order By: Relevance
“…The adhesion of streptococci to solid surfaces has been described as a two‐step process, in which the first step is influenced predominantly by macroscopic substratum properties such as surface free energy 20. Several previous investigations have been focusing on the influence of substratum surface properties on microbial adhesion in vitro 20–27 and in vivo 28–30. Judging from these studies' findings, it can be assumed that substratum surface properties such as surface roughness and surface free energy play pivotal roles in early microbial adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adhesion of streptococci to solid surfaces has been described as a two‐step process, in which the first step is influenced predominantly by macroscopic substratum properties such as surface free energy 20. Several previous investigations have been focusing on the influence of substratum surface properties on microbial adhesion in vitro 20–27 and in vivo 28–30. Judging from these studies' findings, it can be assumed that substratum surface properties such as surface roughness and surface free energy play pivotal roles in early microbial adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, these results can be attributed to differences in the physico–chemical surface properties of different streptococcal strains. In addition to these aspects, it has been argued that surface free energy is presumably more directly related to the binding force rather than to the number of bacteria per surface area 21. Moreover, Sardin and co‐workers assumed that the ratio of dispersive and polar components has a higher importance for bacterial adhesion to prosthetic materials than the total surface free energy or hydrophobicity 27.…”
Section: Discussionmentioning
confidence: 99%
“…: (i) the lower binding force between bacteria and low-energetic surface; (ii) the selectivity in the bacterial adhesion. The first statement is based on the in vitro study of Van Pelt et al (1985) which illustrated that the solid s.f.e. was directly related to the binding force of bacteria rather than to the nutnber of bacteria per surface area, and oti an in vivo study of who found a weak binding of dental plaque on surfaces with a low s.f.e.…”
Section: Discussionmentioning
confidence: 99%
“…The reversibility of oral streptococcal adhesion to substrata with di¡erent wettability after replacing a bacterial suspension by the suspending £uid appeared greater when vG adh s 0 than when vG adh 6 0 with vG adh calculated from Eqs. 7 and 8 [177,178]. Also, when the kinetics of adhesion was followed up to a stationary end-point, it was observed that at the strain level, oral streptococcal adhesion to di¡erent substrata showed strong relationships between adhering numbers and vG adh [149,179].…”
Section: Microbial Adhesion To Substrata and The Thermodynamic Approachmentioning
confidence: 98%